Combination of glycin and thiotriazolin in a single medicinal form - O. V. Khromylova (Zaporozhye State Medical University, 2019)
The beginning of this millennium was marked by significant spread of cardiovascular disease, which took 1-2 place in the mortality structure of industrialized countries. Certain interest is paid to glycine, as a promising primary neuroprotector. It provides the normal functioning of NMDA receptors, due to its effect on glycine sites, which has a metabolitotropic and energotropic effect. There is evidence of the ability of anti-oxidant thiotriazoline to potentiate the therapeutic effect of neuro-metabolic cerebroprotectors. Therefore, it is interesting to create a new combined drug based on glycine and thiotriazoline. Objective - to substantiate the possibility of combining glycine with thiotriazolin in the same dosage form with the help of derivatographic research. Materials and methods of research. As objects of thermogravimetric research, the following substances were used: substances of thiotriazolin (manufacturer: State Enterprise "Plant of chemical reagents" of the Scientific-technological complex "Institute of Single Crystals" of the National Academy of Sciences of Ukraine), glycine (Pharmaceutical Co., Ltd, China), glycine-thiotriazoline blend prepared at the Department of Pharmaceutical Chemistry of ZSMU. The thermographic analysis was carried out on the device of the derivatographer "Shimadzu DTG-60" (Japan) with a platinum-platinum-rhodium thermocouple when heated in aluminum crucibles (from 18 ºC to 250 ºC). As a reference substance, α-Al2O3 was used. The heating rate was 10 °C per minute. The weight of the studied samples was from 13.43 mg to 28.68 mg. Derivatographer graphically recorded the data in the form of curves T, DTA, TGA. Results. In the course of the work, a thermogravimetric analysis of the substance thiotriazoline, glycine, and glycine-thiotriazoline was performed. Thus, it was found that when the mixture of glycine and thiotriazoline is heated up to 118 ºC, the substances remain in the form of powders, and with subsequent heating the mass of the sample decreases. Therefore, we believe that in the technological process of manufacturing dosage forms, it is expedient to carry out technological operations at a temperature not exceeding 118 ºС. Conclusions. According to the obtained data of thermogravimetric analysis of glycine substance, thiotriazoline, mixtures of glycine-thiotriazolin should be noted. It has been found that the mixture of thiotriazoline and glycine is a mixture of active substances that do not interact with each other and may be in the same dosage form as tablets.